Current endoscopic closure techniques for the management of gastrointestinal perforations. (February 2022) - Staudenmann, Dominic; Choi, Kevin Kyung Ho; Kaffes, Arthur John; Saxena, Payal
Acute gastrointestinal perforations occur either from spontaneous or iatrogenic causes. However, particular attention should be made in acute iatrogenic perforations as timely diagnosis and endoscopic closure prevent morbidity and mortality. With the increasing use of diagnostic endoscopy and advances in therapeutic endoscopy worldwide, the endoscopist must be able to recognize and manage perforations. Depending on the size and location of the defect, a variety of endoscopic clips, stents, and suturing devices are available. This review aims to prepare and guide the endoscopist to use the right tools and techniques for optimal patient outcomes.